Pregnancy and physical exercise: myths, evidence and recommendations. - Gouveia, Raquel (2007)
In recent years there has been a great increase of scientific research regarding physical exercise during pregnancy. Nevertheless, many doubts persist leading to a decrease of its practice. We aimed to evaluate the main factors that influence the practice of physical activity during pregnancy and mothers' knowledge regarding its effects. Physical activity has decreased significantly, although it was higher in nulliparous mothers, with higher educational level, employment and between 25 and 34 years old. Mothers who practiced exercise during pregnancy breastfed longer. No correlation was found concerning birth weight, gestational age or obstetric pathology. Although most mothers understand the benefits of physical activity in pregnancy, that doesn't seem to translate in an increasing practice. We believe there should be an increased awareness of health professionals in order to promote controlled physical exercise in pregnant woman.